Natural indoor climate in St. Charles Borromeo chapel in Telc - Hnilica, Ondřej; Bichlmair, Stefan; Fečer, Tomáš; Plášek, Josef (CLIMA 2022 conference, 2022)
The memorial chapel of St. Charles Borromeo from 1664 in town Telc includes the fresco-secco mural painting in the dome. The natural indoor climate with a height of 12.1 m is analysed for the preventive conservation of the original mural painting. This hygrothermal analysis in the period 2018 - 2021 shows the average indoor air temperature of 10.2 Â°C and indoor air relative humidity of 75.1 % r.h. This natural indoor climate shows the frequency of Frost risk in 10.72 % days per year, Microbiology risk in 4.85 % days per year, and Dryness effect in 0.01 % days per year. The vertical stratification of indoor climate is obtained for air temperature up to 5.2 K and -24.1 % r.h. for relative humidity. This natural indoor climate in the St. Charles Borromeo chapel is significantly dependent on outdoor weather with time-lag 2 hours.